Mixed fare Jann Parry on the Royal Ballet at the London Coliseum - Parry, Jann (Dance Books Ltd., Alton,Hampshire (UK), 1998)
PALABRAS CLAVE: Royal Ballet, Darcey Busell, Manon, The Sleeping Beauty, Igor Zelensky, Jonathan Cope, Sylvie Guillem.